Improvement of the foamability of sparkling base wines by the addition of Acacia gums. (30th May 2020) - Apolinar-Valiente, Rafael; Salmon, Thomas; Williams, Pascale; Nigen, Michaël; Sanchez, Christian; Marchal, Richard; Doco, Thierry
Highlights: Bentonite treatment causes a loss of foamability in base wines. Acacia senegal gum enhances the foamability in 63% of bentonite-treated base wines. Acacia seyal gum increases the foamability in 88% of bentonite-treated base wines. The composition of gums and gum fractions treatments affects the wine foamability. The different properties of wines impact on their foamability after gums treatments. Abstract: In sparkling wine, foam characteristics are one of the major attributes. The foam quality depends on wine components. Bentonite is added to the base wine to facilitate the riddling process, but causes a loss of foamability. Acacia gum can be used as additive in wine. We have studied if the addition of Acacia senegal gum ( Asen G), Acacia seyal gum ( Asey G) and different Asen G fractions could improve the foamability of different base wines treated with bentonite. The foamability differs depending on the gum or the gum fraction treatment but also on the wine, being these differences linked to some aspects of their respective compositions and molecular parameters. Asen G and Asey G increase the foamability (by Mosalux - sparging procedure), respectively, in five and seven out of eight base wines treated with bentonite. Therefore, Asen G and Asey G are potential treatments increasing the foamability of these wines.